Kontruksi Akad Ijarah Pada Fatwa DSN MUI Tentang Pembiayaan Multijasa - Rahayu, Annisa Eka; Nurhasanah, Neneng (LAA MAISYIR : Jurnal Ekonomi Islam, 2020)
The purpose of this research is to determine the eligibility of multijsa financing agreement based on Fatwa DSN on multijasa financing. Methods of literature research, multidisciplinary, normative juridical approach. Analytical descriptive data analysis. The results show that the contractor may accept a multifamily financing agreement, using the al-Ijadrah agreement or the al-musta'jir agreement where the tenant will re-rent the services he has rented. Later, the LKS makes a purchase or lease of the service or goods for which it is then rented out, and then the LKS can perform the contract of al-ijârah or the sale of al-musta'ir at a higher price and gradually repayment. So this is one of the factors of public interest in the product of multilingual Ijârah according to the needs of the community each year.